Symbolism of the Rural and Suburban Landscape of the Holy Land in the New Testament - Lena Mirošević; Arkadiusz Krasicki; Josip Faričić (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2021)
The article discusses the symbolism of the rural and suburban landscape of the Holy Land in the New Testament. Based on the results of previous geographical and theological (exegetical) research of certain elements of the natural and cultural landscape, and studies of biblical texts and descriptions of landscape motifs in areas where Jesus Christ lived and worked, the article attempts to point out the symbolism that enriches mere facts about the geographical reality of the Holy Land. It has been determined that the most important natural-geographical forms and phenomena are clearly recognized in the rural and suburban landscape of the Holy Land, while the identity of the Jewish community formed by different human activities and ways of life is imprinted in the cultural landscape, which includes a related web of multiple dualities: the real and the imaginary, the natural and the supernatural, and the material and the spiritual.